2007
DOI: 10.1038/nprot.2007.254
|View full text |Cite
|
Sign up to set email alerts
|

Direct ester condensation catalyzed by bulky diarylammonium pentafluorobenzenesulfonates

Abstract: A protocol for ester condensation between equimolar amounts of carboxylic acids and alcohols catalyzed by bulky diarylammonium pentafluorobenzenesulfonate is described. We also present procedures for the synthesis of N-(2,6-diisopropylphenyl)-Nmesitylammonium pentafluorobenzenesulfonate. The present ester condensation proceeds well under mild conditions even without the removal of generated water. The synthesis of N-(2,6-diisopropylphenyl)-N-mesitylammonium pentafluorobenzenesulfonate will take B5 days. The es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…Most of these methods achieved high yield of TEC, although suffered from catalyst deactivation 47 . On the other hand, ATBC is mainly produced from TBC via two methods: direct esterification in the presence of acetic acid 54 and acetylation in the presence acetic anhydride 55 . Currently, different trademarks are already available in the global market, for example, Citroflex A‐2 and Citroflex A‐4, both widely used in different applications including food contact applications 56 .…”
Section: Citrates Biobased Plasticizermentioning
confidence: 99%
“…Most of these methods achieved high yield of TEC, although suffered from catalyst deactivation 47 . On the other hand, ATBC is mainly produced from TBC via two methods: direct esterification in the presence of acetic acid 54 and acetylation in the presence acetic anhydride 55 . Currently, different trademarks are already available in the global market, for example, Citroflex A‐2 and Citroflex A‐4, both widely used in different applications including food contact applications 56 .…”
Section: Citrates Biobased Plasticizermentioning
confidence: 99%
“…Based on the success of DPAT, a series of analogous ammonium salts was similarly prepared and screened for dehydrative glycosylation. In general, catalysts prepared from either dialkylamines (entries 6-7) or less acidic Brønsted acids, such as methanesulfonic acid (pKa (H 2 O) = -1.9, entry 8) [22], benzenesulfonic acid (pKa (H 2 O) = -2.8, entry 9) [17][18][19][20][21], or p-toluenesulfonic acid (pKa (H 2 O) = -2.1, entry 10) [23] were inactive. Only catalysts generated from Brønsted acids having acidity similar to that of triflic acid (pKa (H 2 O) = -14.7), such as perchloric acid (pKa (H 2 O) = -15.2) [24], gave comparable yields (entry 11).…”
Section: Resultsmentioning
confidence: 99%
“…The shift from metal to metal-free catalysis is the current trend for greener and more sustainable chemistry. Arylammonium triflates and bulky diarylammonium arenesulfonates were introduced by Tanabe [15,16] and Ishihara [17][18][19][20][21], respectively, to be effective catalysts for direct dehydrative esterification between carboxylic acids and alcohols in almost equimolar amounts. The local hydrophobic environment provided by the aryl substituents around the reaction center appears to enable condensation to proceed without the need to remove the water produced.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Ishihara's group reported that bulky diarylammonium pentafluorobenzenesulfonates ([Ar 2 NH 2 ] + [O 3 SC 6 F 5 ] − ) were more efficient than [Ph 2 NH 2 ] + [OTf ] − in catalytic activity and selectivity. 3,[5][6][7] They assumed that it is the dimeric cyclic ion pairs composed of two diarylammonium cations ([Ar 2 NH 2 ] + ) and two pentafluorobenzenesulfonate anions ([O 3 SC 6 F 5 ] − ) which could form a "hydrophobic wall" to promote the esterification reactions. Also their steric hindrance could effectively suppress the dehydrative elimination of secondary alcohols to produce alkenes (Scheme 1).…”
mentioning
confidence: 99%
“…Also their steric hindrance could effectively suppress the dehydrative elimination of secondary alcohols to produce alkenes (Scheme 1). 6 In order to reuse these catalysts, several groups had tried to immobilize these types of ammonium salts on the polymer, but complex synthetic process and instability of the polymer at high temperatures limited their application. [7][8][9] In 2005, Hara's group found a new carbon-based solid sulfonic acid, which was prepared by incompletely carbonizing glucose at high temperatures (over 300 °C) to form a carbonbased material first, and then sulfonating it with a large amount of concentrated sulfuric acid.…”
mentioning
confidence: 99%